Ethical, Legal, and Socioeconomic Aspects of Implementing Artificial Intelligence in Tax Administration - Artur Bogucki (Acta Universitatis Lodziensis Folia Iuridica, 2025)
This study examines the integration of artificial intelligence (AI) in tax law and administration, underscoring key ethical, legal, and socioeconomic dimensions. It explores how AI can improve tax compliance and foster innovation, yet simultaneously raising concerns regarding fairness, transparency, and accountability. Specific risks, including data bias, breaches of privacy, and over-reliance on automated risk-scoring, illustrate the need for robust legal frameworks such as the GDPR and the AI Act. Socioeconomic implications – notably labour displacement and income inequality – spotlight the necessity for equitable policies and responsible AI governance. Drawing on Ethical, Legal, and Social Aspects (ELSA) as well as Responsible Research and Innovation (RRI) frameworks, this research provides recommendations for a comprehensive approach, emphasising stakeholder engagement, transparency, and continuous oversight. Ultimately, a balanced blend of technological ingenuity and principled governance is essential to ensure that AI’s transformative potential truly serves the public interest in tax law and administration.